2022
DOI: 10.1186/s13722-022-00286-6
|View full text |Cite
|
Sign up to set email alerts
|

Rationale, design and methods of VA-BRAVE: a randomized comparative effectiveness trial of two formulations of buprenorphine for treatment of opioid use disorder in veterans

Abstract: Background To address the US opioid epidemic, there is an urgent clinical need to provide persons with opioid use disorder (OUD) with effective medication treatments for OUD (MOUD). Formulations of sublingual buprenorphine/naloxone (SL-BUP/NLX) are considered the standard of care for OUD including within the Veterans Healthcare Administration (VHA). However, poor retention on MOUD undermines its effectiveness. Long-acting injectable monthly buprenorphine (INJ-BUP) (e.g., Sublocade®) has the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Available data examining OD risk in patients treated with MET or BUP-SL who continue to use fentanyl supports a protective effect for both options compared to no treatment 15 . To our knowledge, this is the first examination of the potential benefit of BUP-XR in reducing risk of OD, although additional studies are being conducted that may further extend our knowledge on this important question 16–18 …”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Available data examining OD risk in patients treated with MET or BUP-SL who continue to use fentanyl supports a protective effect for both options compared to no treatment 15 . To our knowledge, this is the first examination of the potential benefit of BUP-XR in reducing risk of OD, although additional studies are being conducted that may further extend our knowledge on this important question 16–18 …”
Section: Discussionmentioning
confidence: 84%
“…15 To our knowledge, this is the first examination of the potential benefit of BUP-XR in reducing risk of OD, although additional studies are being conducted that may further extend our knowledge on this important question. [16][17][18] The parsimonious model, selected using a backward algorithm with P > 0.15 as the exclusion criterion, was used for risk adjustment. The outcome variable for the logistic regression model was the occurrence of at least 1 NF-OD event during the study.…”
Section: Discussionmentioning
confidence: 99%
“…10 Another non-randomized trial in Australia investigating XR-BUP in custodial settings showed treatment retention and outcomes were comparable to those observed in community settings and other MOUD (ie, methadone). 11 Clinical trials comparing XR-BUP and SL-BUP in other populations with OUD, such as pregnant persons 12 and veterans, 13 are underway in the United States. Additionally, an ongoing clinical trial is testing different doses and formulations of buprenorphine (ie, standard dose SL-BUP, high dose SL-BUP, and XR-BUP) as well as tapering strategies.…”
Section: Introductionmentioning
confidence: 99%